2022
DOI: 10.3390/f13010115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Structure and Ecological Function of an Extreme Landscape in a Tropical Region of West Java, Indonesia

Abstract: An extreme landscape is a spatially heterogeneous area with unusual topography that is prone to natural disasters but still exhibits interrelated structures and functions. One of the important functions of an extreme landscape is its ecological function. This study aimed to determine the structure and reveal the ecological functions of an extreme landscape in a tropical region of West Java, with special reference to Rongga Sub-district. The method used was a combination of remote sensing techniques and geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The Malayan pangolin is a species of mammal that avoids human interaction. This research supports the results of a previous study, which showed that the sensitivity of this species to human activity is very high, even though it can adapt to different types of forest cover in plantations or natural forests, provided food is abundant [86]. In the Bukit Barisan National Park, this species has been found to avoid areas that are disturbed by human activity, such as roads and settlements, and threats, such as poaching [87,88].…”
Section: Discussionsupporting
confidence: 89%
“…The Malayan pangolin is a species of mammal that avoids human interaction. This research supports the results of a previous study, which showed that the sensitivity of this species to human activity is very high, even though it can adapt to different types of forest cover in plantations or natural forests, provided food is abundant [86]. In the Bukit Barisan National Park, this species has been found to avoid areas that are disturbed by human activity, such as roads and settlements, and threats, such as poaching [87,88].…”
Section: Discussionsupporting
confidence: 89%
“…Examples include hedges, ponds, individual trees, trees in lines or groups, field margins and stone or earth walls [ 10 , 11 ]. LFs have numerous functional uses, such as the provision of windbreaks and shelter for livestock, regulation of, and protection from, soil erosion, management of water quantity and quality, enhancement of air quality, CO2 sequestration, as well as the maintenance and protection of biodiversity [ 9 , 11 – 16 ].…”
Section: Introductionmentioning
confidence: 99%